PHYSICOCHEMICAL PROPERTIES OF TEA (Camellia sinensis) SEED OIL AND ITS APPLICATIONS - Sahrial Sahrial; Emanauli Emanauli; Meri Arisandi (Jurnal Agroindustri, 2017)
Tea (Camellia sinensis) is widely grown for its leave sand is commercialized as black tea. Product diversification and value addition are currently are of great interest. This study provides data on the physicochemical properties of tea seed oil from Kayu Aro, Jambi Province. Extraction using-hexane was employed to obtain tea seed oil followed by physical-chemical analysis to assess its properties. Physicochemical properties, namely oil yield, density, refractive index, viscosity, turbidity, color, and melting point, as well as free fatty acid, iodine value, peroxide value, and saponification were determined. The oil yield is up to 14% (dB), density is 882.5±5.5kg/m3, refractive index is 1.48±0.20, viscosity is 64.1±0.2 Pa.s, turbidity is 0.88, color 47.0 (L),34.6 (C) and 95.3 (h) as well as free fatty acid 0.39-0.92%, iodine value 29.63-30.87gI2/100g, peroxide value 0.019-0.417 meq O2/100g, and saponification 127.721-168.382. Tea seed oil is stable and can be a potential source of edible and non-edible applications, such as natural nutraceutical,  pharmaceutical, and cosmetic products